2019
DOI: 10.3389/fbioe.2019.00179
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Composite Biomaterials for Neural Regeneration

Abstract: Nervous system damage caused by physical trauma or degenerative diseases can result in loss of sensory and motor function for patients. Biomaterial interventions have shown promise in animal studies, providing contact guidance for extending neurites or sustained release of various drugs and growth factors; however, these approaches often target only one aspect of the regeneration process. More recent studies investigate hybrid approaches, creating complex materials that can reduce inflammation or provide neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 110 publications
0
24
0
Order By: Relevance
“…Damaged dopaminergic neurons may accelerate the distribution of magnetic nanoparticle-based hASCs. Interestingly, recent reports showed that magnetic nanoparticles cause stem cells to differentiate into neurons and improve survival and growth of neurons [ 22 , 23 ]. Thus, the distribution of targeted hASCs using magnetic nanoparticles may be crucial in the treatment and management of PD, although further research is needed to elucidate related mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Damaged dopaminergic neurons may accelerate the distribution of magnetic nanoparticle-based hASCs. Interestingly, recent reports showed that magnetic nanoparticles cause stem cells to differentiate into neurons and improve survival and growth of neurons [ 22 , 23 ]. Thus, the distribution of targeted hASCs using magnetic nanoparticles may be crucial in the treatment and management of PD, although further research is needed to elucidate related mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic nanoparticles are powerful vehicles that can pass the blood-brain barrier and can be widely employed in the diagnosis and treatment of diseases, including as contrast agents for magnetic resonance imaging (MRI), drug delivery, or specific cell delivery and tracking [ 20 , 21 ]. Magnetic nanoparticles reportedly improve targeting of stem cells and efficacy of stem cell-based therapy [ 22 , 23 , 24 ]. Furthermore, magnetic nanoparticle-based hASCs tracking may be a major field for regenerative medicine, including PD.…”
Section: Introductionmentioning
confidence: 99%
“…Many different biomaterials have been developed to modify the neural injury environment and promote subsequent axonal regeneration for the purpose of enabling functional recovery. [34][35][36][37][38][39][40] Hydrogels can be injected to fill irregular injury sites, used to deliver or sequester various molecules, and influence the activity of neural cells. [34,35,39] Hydrogels can also be implemented as intraluminal fillings in nerve guidance conduits to facilitate uniform cell infiltration as well as provide structural support to prevent conduit collapse.…”
Section: Ecm-mimetic Hydrogels For Neural Tissue Engineeringmentioning
confidence: 99%
“…The first attempt toward application of magnets was made at the Pitié-Salpêtrière Hospital in Paris (Richet, 1880). Since the twenty-first century, magnetic materials have been used more widely in medicine, such as in breast-cancer therapy (Zheng et al, 2018), treatment of bacterial infections (Xu et al, 2019), cardiovascular repair (Vosen et al, 2016b), neural regeneration (Funnell et al, 2019), and especially in the skeletal system (Thevenot et al, 2013).…”
Section: Biological Effects Of Magnetic Fields On the Bodymentioning
confidence: 99%